Kinetics and dynamics of the peripheral neurokinin-1 receptor antagonist SLV317 in healthy individuals - Hesse, Christiane; Luntz, Steffen P.; Siedler, Heike; Unnebrink, Kristina; Mikus, Gerd; Bruijn, Marianne; Zondag, Edu; Vries, Michiel; Seibert-Grafe, Monika; Haefeli, Walter E. (British journal of clinical pharmacology, 2006)
Aims To investigate the pharmacokinetics and the pharmacodynamic effects in dorsal hand veins of the neurokinin-1 receptor antagonist SLV317. Methods In a randomized, double-blind, placebo-controlled cross-over study 19 healthy men received a single oral dose of SLV317 or placebo. Blood samples were collected for analysis of SLV317 plasma concentrations and the inhibition of the venodilator response to substance P was evaluated using the hand vein compliance method. Results Administration of 250 mg SLV317 as an oral solution was well tolerated and resulted in mean peak plasma concentrations (± SEM) of 77 ± 9 ng ml−1 within 47 ± 3 min; the mean half-life was 9.9 ± 1.6 h. In hand veins preconstricted with phenylephrine, local infusion of substance P resulted in a mean venodilation of 56 ± 8% and 49 ± 6% (P = 0.91) before administration of SLV317 or placebo, respectively. SLV317 caused a substantial inhibition of substance P-induced venodilation, whereas placebo had no effect (P < 0.001). The maximum antagonizing effect of SLV317 averaged 95 ± 8% and was observed after 1.47 ± 00.24 h. Correspondingly, the mean area under the effect curve after administration of SLV317 [278 ± 67% h−1; 95% confidence interval (CI) 198, 358] was significantly higher compared with placebo (49 ± 12% h−1; 95% CI −24, 122; P < 0.001). Conclusions This study demonstrates that the neurokinin-1 receptor antagonist SLV317 is an orally active and highly effective antagonist of substance P-induced effects in humans.